Cointegration and Causality Between Exports and Production in Valle del Cauca (Colombia) - Alonso-Cifuentes, Julio César; Mueces-Bedón, Brigitte Vanessa (Sociedad y Economía, 2022)
This paper investigates the validity of the export-led growth (ELG) hypothesis and the growth-driven exports (GDE) hypothesis for Valle del Cauca. We use annual data (1960-2015) and sectoral analysis (1975- 2015) to complement the more traditional aggregate analysis in the literature. This document makes two contributions. First, it includes an analysis for the sugar, confectionery, detergents, and paper production sectors. Second, this article uses for the first time a new partial causality technique to determine the validity of these two hypotheses. The results show that there is no evidence to support the ELG hypothesis at either the aggregate or sectoral level. On the contrary, evidence in favor of the GDE is found. These results have a profound impact on economic policy, because exports are not the engine of economic growth in this sector.